A new, more dependable methodology for the use of transcranial Doppler ultrasonography in the management of subarachnoid haemorrhage - (:unkn) unknown (SPRINGER WIEN, 1996)
The role of transcranial Doppler ultrasound (TCD) in clinical decision making about vasospasm due to subarachnoid haemorrhage (SAH), shows a great variation according to neurosurgical clinics. In this prospective study, a total of 143 patients, admitted to Marmara University Department of Neurosurgery between January 1991 to March 1995 and treated surgically with the diagnosis of aneurysmal SAH, were examined by TCD. Eighty of these patients fulfilled the requirements for inclusion. In order to increase clinical dependability of TCD, a new grading system is proposed and tested in comparison with the one previously used, which takes absolute flow velocities as the main parameter in grading. The new, individually based TCD grading system is proposed to minimize the pitfalls caused by proximal stenosis, wide range of normal Vm values and proximally evolving vasospasm. We concluded that: 1) The new, individually based TCD grading system has a high degree of clinical dependability. 2) Daily TCD examinations supply reliable predictive information about developing delayed ischaemic deficit (DID). If a TCD Gr II patient shows an increase of 35 cm/sec (in 24 hours) in Vm value, his probability of developing DID was found to be 60% (p < 0.05); if a TCD Gr B III patient shows the same rate of increase in Vm, his probability of developing DID was 80% (< 0.05). 3) TCD has an important clinical role in decision making about the management of SAH patients. 4) Surgical manipulation causes a reversible increase of one or two TCD-grades in the early postoperative days.
Keywords: blood flow velocity; cerebral aneurysm; delayed ischaemic deficit; transcranial Doppler sonography; vasospasm; CEREBRAL-ARTERY VASOSPASM; CEREBROVASCULAR SPASM; BLOOD VELOCITY; HEMORRHAGE; SONOGRAPHY; DIAGNOSIS; ULTRASOUND; HYPERTENSION; HEMODYNAMICS